1990
DOI: 10.1177/00220345900690121301
|View full text |Cite
|
Sign up to set email alerts
|

The Crown Odontoblasts of Rat Molars from Primary Dentinogenesis to Complete Eruption

Abstract: The involution of crown odontoblasts after primary dentinogenesis in teeth of limited eruption is discussed. The odontoblasts of rat first lower molars were analyzed morphometrically from the tenth day to the 40th day of age, i.e., from the late phase of primary dentinogenesis to complete eruption. All the organelles underwent atrophy, but at different rates. In particular, the membranes of the endoplasmic reticulum decreased progressively in surface area from day 10 to day 40, whereas those of the Golgi appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…It was reported that the area and ratio of the cytoplasm, rER and Golgi apparatus of the odontoblast were decreased gradually from the crown (PN10, 14,16) to erupted (PN40) stage in rat molar development. 23 In this study, the morphological characteristics of odontoblasts were similar to those of previous rat development (Figs. 3(a-c)).…”
Section: Resultssupporting
confidence: 85%
“…It was reported that the area and ratio of the cytoplasm, rER and Golgi apparatus of the odontoblast were decreased gradually from the crown (PN10, 14,16) to erupted (PN40) stage in rat molar development. 23 In this study, the morphological characteristics of odontoblasts were similar to those of previous rat development (Figs. 3(a-c)).…”
Section: Resultssupporting
confidence: 85%
“…It has been postulated that primary dentinogenesis ends when the crown is complete. This assumption is supported by the finding that cell organelles undergo atrophy at that point in rat molars (50). Primary dentinogenesis has also been timed to end when teeth becomes functional (12) and when root formation is complete (7,51).…”
Section: Circumpulpal Dentin Primary and Secondary Dentinmentioning
confidence: 93%
“…The granules containing fibrillar elements (the abacus-like vesicles) on the other hand, are morphologically similar to one type of cytoplasmic bodies closely related to the Golgi complex. Furthermore, these abacus-like vesicles stained positive for acid phosphate activity, and therefore have been elucidated to be the granules relating to the secretion and digestion of the procollagen in both the functioning and resting OBs by many previous studies (Tsuboi, 1968;Nagai, 1970a;Takuma and Nagai, 1971; Weinstock and Leblond, 1974;Leblond, 1989;Romagnoli et al , 1990;Linde and Goldberg, 1993). In the present SEM using the AODO method, we observed many empty vesicles (secretory-granule-like structures) near the nucleus and the cell membrane and some large membranous structures containing many small vesicles (multivesicular bodies; MVBs) in the functioning and resting OBs.…”
Section: Discussionmentioning
confidence: 92%
“…There have been many transmission electron microscopy (TEM) studies on the morphological changes and the fine structure related to secretion and absorption by odontoblasts (OBs) at different developmental stages (Reith, 1968;Tsuboi, 1968;Takuma and Nagai, 1971; Weinstock and Leblond, 1974;Gartner et al , 1979;Goldberg and Septier, 1985;Suzuki, 1985;Rule, 1986;Avery, 1987;Nagai, 1970a;Nagai, 1970b;Leblond, 1989;Romagnoli et al, 1990;Linde and Goldberg, 1993). The occurrence of various kinds of cytoplasmic bodies closely related to the Golgi complex and the smooth (agranular) endoplasmic reticulum (sER) has been reported during early and late dentinogenesis, respectively, in some of these studies (Tsuboi, 1968;Takuma and Nagai, 1971;Romagnoli et al, 1990), while others have suggested that the Golgi elements and some cytosomes (lysosomes) are organelles concerned with autodigestion and regulatory functions of the OBs at different developmental stages (Nagai, 1970a;Romagnoli et al, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation